Menelaah Konsep Li’an Suami Sebagai Cara Mencegah Sanksi Menuduh Zina dari Kaca Mata Medis dan HAM Dalam Konteks Kekinian - Anwar, Muhamad Ridho; Musip, Muhammad (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2024)
Background. Li’an is used as an alternative to free a husband from qozhaf sanctions (accusing him of adultery), with the condition that the husband cannot present 4 bayyinah (witnesses) as witnesses to his wife's unfaithful actions. One of the legal consequences of li'an is that it confirms the lineage of a child with its father. Aim. Analyzing the husband's Li’an as a way to prevent sanctions for accusing him of adultery from a medical and human rights perspective Methods. This library research uses a descriptive-qualitative approach. Literature comes from authoritative data, such as classical jurisprudence books, tafsir, articles and books. The data was analyzed qualitatively and presented in descriptive form. Results. DNA test results can be used as evidence of Qorinah (signs), in the category of evidence in the form of allegations. It’s can clarify the child's lineage status, whether it is a child from the mother's husband or from another man, and can also clarify the punishment that will be received by a husband who accuses his wife of infidelity, whether he will be subject to had qozhaf or not. The concept of li’an from a human rights perspective is appropriate, because in li’an there are human rights that must be fought for, namely children's human rights. The state is expected to pay attention to the human rights of li’an children, through regulations that regulate scientific evidence through DNA testing to clarify the status and rights of children.